Frequency of Iron Deficiency Anaemia in Exclusively Breastfed and Infants Fed on Cow’s Milk - Muhammad Umar Saleem, Hira Khalid, Sana Rehman, Ujala Aymun, Nagham Nawaz Awan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Iron is the most prevalent nutrient deficiency in infants and young children around the world despite its importance for healthy brain development. Infants who drink whole cow's milk or other animal milks are at a greater risk of developing iron deficiency anaemia. In our culture, cow's milk consumption is widespread. There were no local studies available on iron deficiency anemia in infants using different types of milk so need for the present study was felt. Objectives: The objectives of this study were to determine the frequency of exclusively breastfed and cow’s milk fed infants at 3 month of age and to compare the frequency of iron deficiency anemia in exclusively breastfed and cow’s milk fed infants. Study Design: It was a cross-sectional study. Setting and Duration: Research was conducted at the Medical Outpatient Department of The Children’s Hospital and The Institute of Child Health Lahore from 08/02/2022 to 07/08/2022. Material and Methods: This study involved 220 infants of both genders at 3 months of age presenting for vaccination. Outcome variables were frequency of exclusive breast feeding and iron deficiency anemia. All patients' guardians signed an informed consent form. Results: There were 115 (52.3%) male and 105 (47.7%) female patients in the study group. The Hb of the patients ranged from 7.6 g/dl to 14.5 g/dl with a mean of 11.00±1.98 g/dl while the serum iron level ranged from 41 µg/dl to 115 µg/dl with a mean of 67.94±22.99 µg/dl. Majority of the parents (56.4%) belonged to poor class and 46.4% mothers were illiterate. The frequency of exclusive breastfed infants was 45 (20.5%). There was no significant difference in the frequency of exclusive breast feeding across gender (p=0.873), socioeconomic (p=0.900) and educational (p=0.858) status. 76 (34.5%) Infants had iron deficiency anemia. The frequency of iron deficiency anemia was higher among infants on cow’s milk (37.7% vs. 22.2%) as compared to those on exclusive breast feeding however the observed difference was statistically insignificant (p=0.051). Similar insignificant difference was observed across gender, socioeconomic and educational status groups. Conclusion: The frequency of exclusive breastfed infants was 45 (20.5%). There was no significant difference in the frequency of exclusive breast feeding across gender (p=0.873), socioeconomic (p=0.900) and educational (p=0.858) status. 76 (34.5%) Infants had iron deficiency anemia. The frequency of iron deficiency anemia was insignificantly higher among infants on cow’s milk (37.7% vs. 22.2%; p=0.051) as compared to those on exclusive breast feeding. Similar insignificant difference was observed across gender, socioeconomic and educational status groups. Keywords: Exclusive Breast Feeding, Cow’s Milk Feeding, Iron Deficiency Anemia